Yak Milk Production in North-East India: Prospect of Yak Herding in Arunachal Pradesh (Indian Journal of Animal Production and Management, 2024)
Dairy farming plays a crucial role in achieving  Sustainable Development Goals (SDGs) by  contributing to various aspects of sustainability  such as household income; increased direct  consumption of healthy and nutritious food;  women's empowerment and gender equality. The  dairy sector in India is dominated by cows and  buffalos to produce milk and milk derivatives.  However, rearing of Yak is commonly found in  certain parts of India like Sikkim, Ladakh and  Arunachal Pradesh nestled in lofty peaks of the  Himalayas with rugged landscapes. In these  climatic zones, yak herding communities have  sustained themselves for centuries, preserving their  rich cultural heritage. The yak herders have  preserved their unique age-old practice of  traditional yak rearing and Indigenous knowledge.  In these states, the diminishing pastoral  communities are engaged in the production of milk  and milk derivatives such as fermented cheese and  butter derived from yak. From the perspective of yak  farming a smaller number of studies were  conducted that too in Western countries. In the  above context, the present study focuses on  understanding the present scenario and prospects  of yak herding relative to their current dairy products  marketing and production models. The study also  emphasizes the problems and opportunities in the  field of yak herding in Northeast India, with special  reference to Arunachal Pradesh.
Keywords: Yak herding; Indigenous knowledge; Milk production; Marketing; SDGs